Ecological distribution of the shrimp Pleoticus muelleri (Bate, 1888) (Decapoda : Penaeoidea) in southeastern Brazil - Costa, R. C.; Fransozo, A.; Pinheiro, A. P. (Kluwer Academic Publ, 2004)
The abundance and ecological distribution of the shrimp Pleoticus muelleri as a function of certain environmental factors were investigated from January 1998 through December 1999 in the region of Ubatuba, São Paulo, Brazil. The collections were made monthly in the bays of Ubatumirim (UBM), Ubatuba (UBA) and Mar Virado (MV). Each bay was divided into six sampling transects, four transects parallel to the shoreline and two near the rocky shores on the opposite side. We employed a commercial shrimp boat equipped with two double-rig nets. A total of 6252 shrimp were collected, including 3321 from MV, 1467 from UBM, and 1464 from UBA. Most of the shrimp were caught in the deeper, higher-salinity areas. The high abundance of P. muelleri observed in the southern part of the region studied was related to a sediments with a higher percentage of silt and clay. The numbers of P. muelleri were positively correlated with periods of cooler temperatures. Thus, temperature and the type of sediment were determinant factors in the distribution of P. muelleri in this region.
Keywords: Pleoticus muelleri; distribution; Penaeoidea; Brazil